Adiabatic laminar burning velocities of C3H8-O2-CO2 and C3H8-O2-N2 mixtures at ambient conditions-PART II: Mechanistic interpretation. (15th September 2020) - Liu, Guangyi; Zhou, Junhu; Wang, Zhihua; Yang, Weijuan; Liu, Jianzhong; Cen, Kenfa
Highlights: Global parameters of laminar premixed C3 H8 -O2 -CO2 and C3 H8 -O2 -N2 mixtures. Construction and validation of one-step model using large activation energy assumption. Mechanistic interpretation of the dilution effect on laminar burning velocity of C3 H8 -O2 -CO2 and C3 H8 -O2 -N2 mixtures. A correlation between laminar burning velocity and maximum (H + OH + O) concentration is proposed. Isolation of chemical, transportation and thermal effect of CO2 replacement of N2 in C3 H8 -O2 mixture. Abstract: The effect of diluents on the laminar burning velocity of the premixed C3 H8 -O2 -N2 and C3 H8 -O2 -CO2 mixtures was numerically studied. Global flame parameters including adiabatic flame temperature ( Tad ), overall reaction order ( n ), activation energy ( Ea ), Zeldovich number ( Ze ) and Lewis number ( Le ) were calculated. Results show that the N2 /CO2 alters all flame parameters. Based on asymptotic analysis for one-step overall reaction, these parameters correlates the laminar burning velocity. The change of Arrhenius effect, combination of thermal and chemical effect is the dominant factor, compared to the change of transport effect. Sensitivity analysis revealed that thermal effect is the dominant factor in Arrhenius effect. The correctness of one-step model was validated with experimental and numerical results. Detailed mechanism model analysis illustrates the linear correlations between laminar burning velocity and maximum (H + OH + O) concentration. The chemical effect of CO2 replacement of N2 in oxidizer is smaller than the thermal effect but much bigger than the transport effect in the calculation domain. The chemical effect of CO2 changes drastically with equivalence ratios and oxygen fractions.